Research on the Optimization of University Library Services Supported by Information Technology: A Case Study of S University in Hebei Province - Zhao , Huan (International Journal of Computer Science and Information Technology, 2025)
With the advent of the intelligent era, cutting-edge information technology has permeated various global fields. To provide better services to students and faculty, university libraries must adapt to the ever-changing information technology environment and meet the evolving needs of their users. Diversification of services has become an inevitable requirement for university libraries to implement technology-supported services. Taking the library of S University in Hebei Province as a research object, this paper explores the practical approaches and prospects for optimizing library services from the perspective of information technology support. By analyzing the application of information technology in resource management, user services, and smart library construction, it proposes service optimization strategies centered on user needs and technology integration, aiming to enhance library service efficiency and user satisfaction.